Scaling inter‐tablet coating variability in a horizontal rotating drum. Issue 9 (5th May 2017) - Ban, J.; Kumar, R.; Agarwal, S.; Wassgren, C.
Abstract : This study investigates how the drum‐to‐particle diameter ratio ( D / d ) affects the surface speed and interparticle coating variability in geometrically similar coaters. Discrete element method simulations were used to model particle movement in different‐sized, cylindrical drums with identical particle diameters, Froude numbers, fill volume fractions, and spray characteristics. The dimensionless streamwise surface speed profiles become increasingly symmetric as D / d increases, with the maximum speed increasing with D / d . The relationship between the maximum dimensionless speed and D / d is fit well with a power‐law expression. Interparticle coating variability decreases with the square root of the number of drum revolutions after a sufficiently large number of drum revolutions. Increasing D / d increases, in a logarithmic manner, the number of drum revolutions required to reach a given degree of coating variability. A similar logarithmic coating variability trend was observed in simulations using almond‐shaped pharmaceutical tablets, suggesting that the trend is independent of tablet shape. © 2017 American Institute of Chemical Engineers AIChE J, 63: 3743–3755, 2017